PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN BEBEK KALEYO CABANG TEBET JAKARTA - Fenny Nofriday; Nova Eviana (Panorama Nusantara, 2016)
This research is aimed to measure the influences of service quality and location toward the customers’ purchasing decision of Bebek Kaleyo Tebet Restaurant. The population of the research are the consumers of Bebek Kaleyo Tebet Restaurant and a hundred of them are taken as respondents using purposive sampling technique. Method of analysis uses Multiple Regression analysis. The result shows that service quality and location have positive and significant influence toward purchasing decisions. Based on the analysis of statistical data, indicators on research are valid and reliable. By testing the assumptions of classical regression model, Gaussian with a value of 0.05 > significance i.e. non 0,870, multicollinearity problem and there is no heterokedastisitas. Order partially from each of the most influential variable is variable of location with the influence of 14,66% whereas the least influential variable is quality of service with the influence of 0.72%. Restaurant’s management therefore needs to pay more attention and highlight other factors (quality of the product, price, promotion, etc.) that may influence more over customers’ purchasing decisions.